Numbers Games. - Shriberg, Amy Burke (Dissent (0012-3846))
Points out that the official unemployment rate of the U.S. reflects a rather narrow definition of unemployment and obscures debates about the overall health of the economy and its ability to provide decent family-supporting jobs to all citizens. Observation that in order to be classified as unemployed, individuals must meet several Bureau of Labor Statistics criteria; Failure to account for many people without jobs who are available and want to work.